2020
DOI: 10.1101/2020.04.30.070326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing the body morphology of the first metacarpal in the Homininae using 3D geometric morphometrics

Abstract: 26Objectives: Extinct hominins can provide key insights into the development of tool use, 27with the morphological characteristics of the thumb of particular interest due to its 28 fundamental role in enhanced manipulation. This study quantifies the shape of the first 29 metacarpal's body in the extant Homininae and some fossil hominins to provide 30 insights about the possible anatomical correlates of manipulative capabilities. 31 Materials and methods: The extant sample includes MC1s of modern humans (n=42),… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…In support of our third hypothesis, we found no evidence to support an allometric relationship between metacarpal size (using either centroid size or maximum metacarpal length) and external shape (using Procrustes aligned coordinates). Previous studies of metacarpal shape have identified weak or no allometric relationships between shape and size in hominoids (e.g., Bardo et al, 2020;Bowland et al, 2021;Galletta et al, 2019: Morley et al, 2020Niewoehner, 2005), and suggests that variation in activity, among other factors such as genetics, may be one of the main factors driving variation in metacarpal shape in this study sample. However, without detailed profiles of individuals within our study sample, we must assume that differences in sex, age, hormones (in addition to activity), and the interaction between them all, may also be in part responsible for the morphological differences we find across our sample.…”
Section: Metacarpal External Shape Variationmentioning
confidence: 48%
See 2 more Smart Citations
“…In support of our third hypothesis, we found no evidence to support an allometric relationship between metacarpal size (using either centroid size or maximum metacarpal length) and external shape (using Procrustes aligned coordinates). Previous studies of metacarpal shape have identified weak or no allometric relationships between shape and size in hominoids (e.g., Bardo et al, 2020;Bowland et al, 2021;Galletta et al, 2019: Morley et al, 2020Niewoehner, 2005), and suggests that variation in activity, among other factors such as genetics, may be one of the main factors driving variation in metacarpal shape in this study sample. However, without detailed profiles of individuals within our study sample, we must assume that differences in sex, age, hormones (in addition to activity), and the interaction between them all, may also be in part responsible for the morphological differences we find across our sample.…”
Section: Metacarpal External Shape Variationmentioning
confidence: 48%
“…In this study, we use whole surface GM to capture the shape of both the proximal and distal articular surfaces and the diaphysis of MC1-5 and combine this with analyses of CSG. We test for allometry on metacarpal shape with the expectation that results will be consistent with previous GM studies that have used solely hominoid samples (Bardo et al, 2020;Bowland et al, 2021;Galletta et al, 2019;Morley et al, 2020;Niewoehner, 2005) and shown size to be a minor contributor to metacarpal shape variation.…”
Section: Measuring Metacarpal Shape and Cortical Bone Structurementioning
confidence: 65%
See 1 more Smart Citation
“…Several of these studies have focused on morphological characters with extensive functional significance, 4 , 8 , 9 , 21 , 22 providing novel insights into hominin behavior on the basis of variation in the three-dimensional (3D) form of the bone’s external aspects 18 , 9 , 10 , 22 or their underlying trabecular structures (e.g., Kivell 4 and Dunmore et al. 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Even though muscle forces comprise a central component of biomechanical efficiency, 22 , 71 past morphological research on fossil hand bones did not address the potential differences across hominin species in muscle force-generating abilities. However, considering that muscle force-producing capacities are known to vary greatly among great apes and even between humans and chimpanzees, 34 assessing the manual dexterity of fossil hominins entirely based on bone geometry is prone to severe misinterpretations regarding their manual dexterity.…”
Section: Methodsmentioning
confidence: 99%